THE RELATIVE INFLUENCE OF ENALAPRIL AND LOSARTAN ON THE DIURNAL PROFILE OF ARTERIAL PRESSURE IN HYPERTENSIVE PATIENTS - V. A. Azizov; L. G. Efendieva (Евразийский Кардиологический Журнал)
Main purpose of our study was to examine the comparative effects of enalapril and losartan on the performance of daily blood pressure monitoring at the patients with hypertension. 100 patients with II stage hypertension participated in this study. Age of patients ranged from 35 to 80 years (32 male; 68 female). Daily monitoring was carried out using 24- hour pressure monitor (CBM-01) serial number 201 001 by standard methods. 50 patients used ACE inhibitor enalapril maleate (KRKA, Sloveniya) in a dose of 5-20 mg / day for 12 weeks. 50 patients received losartan (MRKTD by Brown London) 25-50 mg / day. Received data were statistically processed by methods of medical statistics due to all modern standards. As enalapril, and losartan alone showed an adequate corrective efficacy in the morning of the absolute values of the blood pressure dynamics, «pressure load» indicators, but in a comparative analysis did not reach statistical significance. Each of the drugs showed us an adequate corrective efficacy of the absolute values at the morning blood pressure dynamics, but comparative analysis of statistical significance was not observed. Comparing to Losartan, Enalapril statistics were much better, while average nocturnal blood pressure were better decreased by losartan. In addition, it should be noted that despite the identical effect of the drugs, losartan is better tolerated than enalapril, without any side effects.